PENGEMBANGAN MODUL MATERI MAWARIS BERBASIS PROBLEM BASED LEARNING (PBL) DI MAN 1 NAGAN RAYA - Jannah, Miftahul; Hayati, Hayati; Zulfatmi, Zulfatmi; Syauky, Ahmad (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
Islamic religious education in Madrasah Aliyah plays an important role in shaping students' understanding of Islamic law, including the material of Mawaris. However, Mawaris learning is often considered difficult because of its theoretical nature and the lack of an applicable approach. This study aims to develop a Mawaris material module based on Problem Based Learning (PBL) that can be used as a learning medium in Madrasah Aliyah. This module is designed to improve students' understanding of the Mawaris concept through an approach that focuses on problem solving. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the study indicate that MAN 1 Nagan Raya needs a Mawaris learning module based on Problem-Based Learning (PBL) to improve the quality of learning. The needs analysis revealed that the school does not yet have an interactive and relevant module, so learning tends to be theoretical. Teachers feel that PBL-based modules are very necessary to deliver material effectively and applicable, while students want a more practical approach to facilitate understanding. PBL-based modules are expected to be able to connect theory with real-life practices, improve critical thinking skills, and help students understand the concept of inheritance law better.